An Extension Form of Chiari 1 malformation: A Case Report - Wiryaning Putri, Komang Yunita; Novan Krisno Adji; Ulfa Elfiah; Muhammad Yuda Nugraha (Journal of Agromedicine and Medical Sciences, 2025)
The updated classification of Chiari malformation includes Chiari 1.5 malformation, which explicitly denotes the tonsillar herniation characteristic of Chiari 1 malformation, accompanied by an extended brainstem and a dilated fourth ventricle. We present a Chiari 1 malformation characterized by significant downward herniation of the tonsils and the development of syringomyelia, with no indication of elongation of the fourth ventricle. This example represents an extension of Chiari 1 malformation, which is currently not classified as Chiari 1.5 malformation. A 27-year-old female exhibited cephalic and cervical discomfort for two years. The initial MRI indicated a fall of the cerebellar tonsil beneath the foramen magnum. The midsagittal MRI assessed the degree of tonsillar herniation beneath the foramen magnum. Tonsillar herniation was observed at the C2 level; a spinal MRI revealed syringomyelia affecting the C2 to C3 levels. The patient received a suboccipital craniectomy and C1-C2 laminectomy. There was dural sac pulsation at the C2 level. The patient's cervical discomfort resolved entirely following the surgical procedure. This case represents an extension of Chiari 1 malformation, which is currently not classified as adenotes explicitly 1.5 malformation.